The peasant family and the sacred Cosmos - Garr, Thomas M. (1972)
In the countryside, the basic social, economic, and religious entity is the family, and everything else revolves around it. Furthermore, the ideological basis of the peasant family is its religion. So any agent of social change or adapted pastoral has to take into account that common denominator and the mental structure that supports it. This article will present some data to substantiate these two statements and will end with guidelines for people from the "Westernized" world who find themselves in this situation in the countryside.